Introduction to media in Malaysia - Yusoh, Mohd Helmi (Communication and Media Centre (COMET), IIUM, 2025)
This book represents a starting point a preliminary effort to document Malaysia’s media history. While it provides a foundational overview, our hope is that future editions will expand this work, covering broader and deeper aspects of the Malaysian media experience. By doing so, we aim to contribute to the growing body of knowledge that celebrates and critically examines the media's role in shaping Malaysia’s past, present, and future. In this context, the urgency to reflect on and document these changes cannot be overstated. This volume explores how the digital era has reshaped traditional media forms such as radio, television, newspapers, and advertising. It highlights the resilience and adaptability of the Malaysian media industry, offering valuable insights into its transformative journey and setting the stage for future exploration and discourse. Structured to offer a comprehensive yet accessible narrative, the chapters in this book cover various aspects of Malaysia’s media evolution.